One‐Step Route to Ladder‐Type C–N Linked Conjugated Polymers. Issue 9 (3rd April 2019) - Ren, Xiaojie; Zhang, Hailei; Song, Meining; Cheng, Cong; Zhao, Hongchi; Wu, Yonggang
Abstract: A one‐step synthetic method is demonstrated to construct ladder‐type conjugated polymers without the resource to post‐cyclization procedures. The ladder‐type C–N linked conjugated polymers (P1 andP2 ) and model compounds (1 and2 ) are achieved in high yields. The obtained model compounds and polymers display desirable solubility in commonly used solvents and high thermal stability, which show a promising application in photoelectric material field. Abstract : Ladder‐type conjugated polymers (P1 and P2) are synthesized in high yields based on a one‐step synthetic method. In this process, the cyclization occurs accompanying with the Suzuki coupling to give the ladder‐type conjugated polymers without the resource to post‐cyclization procedures.